Efficient visible-light-driven hydrogen evolution over ternary MoS2/PtTiO2 photocatalysts with low overpotential. (23rd August 2018) - Li, Shasha; Pu, Tingting; Wang, Junjie; Fang, Xueyou; Liu, Yanfei; Kang, Shifei; Cui, Lifeng
Abstract: By surface-decorating PtTiO2 hybrid catalyst with MoS2 nanosheets, we prepared a new MoS2 /PtTiO2 ternary system as high-performance photocatalysts. The ternary MoS2 /PtTiO2 outperforms both the binary MoS2 TiO2 and PtTiO2 systems in photocatalytic hydrogen evolution with an AQY (apparent quantum yield) value of 12.54% at 420 nm, owing to the unique ternary design that creates more efficient electron transport path and electron-hole separation mechanism. Electrochemical characterization showed that the MoS2 /PtTiO2 ternary electrode afford an efficient pathway of photo-excited electrons from TiO2 to surface-decorated Pt nanoparticles using MoS2 and internal Pt nanoparticles as bridges, thus significantly promoting electron transfer, reducing the system overpotential and leading to the activation of more reactive sites. This internal electron transfer pathway (TiO2 → Pt (internal) → MoS2 → Pt (surface)) eliminates the need of other metal cocatalysts because the Pt nanoparticles play two roles of storing the conduction band electrons of TiO2 and acting as co-catalyst for reduction of protons to hydrogen. This unique ternary metal-semiconductor heterojunction for efficient photocatalytic hydrogen evolution provides a meaningful reference for reasonable design of other hybrid photocatalysts. Highlights: A novel ternary system consisted of MoS2 /PtTiO2 has been facilely developed. The MoS2 /PtTiO2 with overpotential show enhanced photo-electrocatalytic performance. The ternary design can improve the photocatalytic HER activity and cyclic stability. The intrinsic electron-transfer behavior is investigated by various electrochemical tests.